Policy Without Delivery: The Breakdown of Primary Health Care Financing in Nigeria - Adu, Adebusola; Owolabi, Babatunde; Okunade, Ibukunoluwa; Eberechukwu, Karen; Obembe, Taiwo (American Journal of Biomedicine and Pharmacy, 2025)
Primary health care (PHC) is the foundation of a good health system. It provides accessible, affordable, and equitable healthcare services. The World Health Organization (WHO) defines PHC as a community-centered approach that delivers comprehensive care ranging from health promotion to disease prevention and treatment care.1 In Nigeria, however, the primary health care (PHC) system faces serious challenges. From inadequate funding to poor infrastructure in most primary care locations, a lack of power supply, and a shortage of health workers. Only about 30–45% of these centers are fully equipped and managed.2 Rural areas are the worst affected, with clinics lacking essential services and staff.3